Early, intermediate and late infectious complications after transcatheter or surgical aortic‐valve replacement: a prospective cohort study. (24th December 2013) - Falcone, M.; Russo, A.; Mancone, M.; Carriero, G.; Mazzesi, G.; Miraldi, F.; Pennacchi, M.; Pugliese, F.; Tritapepe, L.; Vullo, V.; Fedele, F.; Sardella, G.; et al.
Abstract Transcatheter aortic valve implantation (TAVI) has been proposed to treat older surgical high‐risk patients with severe symptomatic aortic stenosis. There are no data regarding short‐term and long‐term infectious complications in these patients. The objective of this study was to define the incidence, aetiology and outcome of early and late infectious complications following TAVI compared with patients >65 years old undergoing traditional surgical aortic replacement (SAR). This was a prospective observational study evaluating all consecutive patients who underwent TAVI or SAR. Follow up was performed up to 1 year after the procedure of valve implantation. Fifty‐one patients underwent TAVI and were compared with 102 patients who underwent SAR. Compared with SAR patients, those who underwent TAVI had lower incidence of early post‐operative (11.7% vs 26.4%, p 0.04), intermediate (5.9% vs 17.6%, p 0.01) and late (7.8% vs 11.7%, p 0.03) infections. Among SAR patients the most common infections were bloodstream infections, pneumonias, urinary tract infections and sternal wound infections. Patients who underwent TAVI had a longer survival without infection (358 days vs 312.9, p 0.006). There were no significant differences in 12‐month crude survival between the two study populations. Despite a high frequency of coexisting illnesses, patients undergoing TAVI develop few infectious complications. TAVI appears to be a reasonable and safe option in high‐risk patients with severe symptomatic aortic stenosis.